2015
DOI: 10.1063/1.4929148
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of complexity in the electroencephalograph activity of Alzheimer's disease based on fuzzy entropy

Abstract: In this paper, experimental neurophysiologic recording and statistical analysis are combined to investigate the nonlinear characteristic and the cognitive function of the brain. Fuzzy approximate entropy and fuzzy sample entropy are applied to characterize the model-based simulated series and electroencephalograph (EEG) series of Alzheimer's disease (AD). The effectiveness and advantages of these two kinds of fuzzy entropy are first verified through the simulated EEG series generated by the alpha rhythm model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…Because the characteristics of those signals are physiologically nonlinear, the advantages of using nonlinear methods vs. conventional linear methods to describe the complex patterns have been shown in several earlierstudies21222324. Our study showed that the optimal PPG analytic program for AF detection included both linear and nonlinear features, which indicates a synergistic rather than a competitive relationship between the linear and nonlinear PPG features.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Because the characteristics of those signals are physiologically nonlinear, the advantages of using nonlinear methods vs. conventional linear methods to describe the complex patterns have been shown in several earlierstudies21222324. Our study showed that the optimal PPG analytic program for AF detection included both linear and nonlinear features, which indicates a synergistic rather than a competitive relationship between the linear and nonlinear PPG features.…”
Section: Discussionsupporting
confidence: 55%
“…Recently, several nonlinear analytical methods had been applied to quantify the complex regulatory dynamics of human biological signals such as heart rate variability21, electroencephalography22, and intracranial pressure23. Because the characteristics of those signals are physiologically nonlinear, the advantages of using nonlinear methods vs. conventional linear methods to describe the complex patterns have been shown in several earlierstudies21222324.…”
Section: Discussionmentioning
confidence: 99%
“…These measures, which include approximate entropy [1], sample entropy [2], fuzzy entropy [4], corrected conditional entropy [3], and permutation entropy [6], are extremely popular for the estimation of conditional entropy in several fields ranging from applied physics to neuroscience, physiology, econometrics, climatology, earth sciences, and others [24,25,2932,37,38,87,88]. …”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to note that non-linearity in the brain is introduced even at the cellular level, since the dynamical behavior of individual neurons is governed by threshold and saturation phenomena [26]. More globally, the brain also presents a really complex and heterogeneous performance, which makes its behavior far from being considered linear [27]. Hence, the use of entropy-based metrics in the described context is completely justified.…”
Section: Introductionmentioning
confidence: 99%